Modeling, Analysis, and Implementation of Series-Series Compensated Inductive Coupled Power Transfer (ICPT) System for an Electric Vehicle - Moustapha Elwalaty; Mohamed Jemli; Hechmi Ben Azza (Journal of Electrical and Computer Engineering)
This paper focuses on the modeling and implementation of an Electric Vehicle (EV) wireless charging system based on inductively coupled power transfer (ICPT) technique where electrical energy can be wirelessly transferred from source to vehicle battery. In fact, the wireless power transfer (WPT) system can solve the fundamental problems of the electric vehicle, which are the short battery life of the EV due to limited battery storage and the user safety by handling high voltage cables. In addition, this paper gives an equivalent electrical circuit of the DC-DC converter for WPT and comprises some basic components, which include the H-bridge inverter, inductive coupling transformer, filter, and rectifier. The input impedance of ICPT with series-series compensation circuit, their phases, and the power factor are calculated and plotted by using Matlab scripts programming for different air gap values between the transmitter coil and receiver coil. The simulation results indicate that it is important to operate the system in the resonance state to transfer the maximum real power from the source to the load. A mathematical expression of optimal equivalent load resistance, corresponding to a maximal transmission efficiency of a wireless charging system, was demonstrated in detail. Finally, a prototype of a wireless charging system has been constructed for using two rectangular coils. The resonant frequency of the designed system with a 500 × 200 mm transmitter coil and a 200 × 100 mm receiver coil is 10 kHz. By carefully adjusting the circuit parameters, the implementation prototype have been successfully transferred a 100 W load power through 10 cm air gap between the coils.